Recent price trend in Ireland - Geary, R.C.; Pratschke, J.L.; Henry, E.W. (Economic & Social Studies, 1970)
In the first section we set out the major price trends since 1958 and indicate the principal cause of price inflation. In later sections we examine the effects of productivity, wage and profit rates, prices of imports and exports on (a) the general level of internal prices and (b) prices in different sectors of the economy, using the Input, Output technique, with particular regard to what seems likely to happen price-wise in 1970.
Keywords: Economics - Ireland; Inflation - Ireland